Audit Energi dan Analisis Peluang Penghematan Konsumsi Energi Listrik Pada Rumah Tangga - Purbaningrum, Sanurya Putri (Media Mesin, 2014)
Population growth fastly causes the amount of energy consumption is increasing. Accretion of energy consumption without the addition of the source will cause the disruption of existing energy distribution system. Meanwhile, alternative energy development takes a long time while the demand for energy cannot be postponed. To overcome this, the goverment has issued Goverment Regulation No. 70 Year 2009 on Konsevarsi Energi. Main part of energy conversion includes an audit of energy that knowing the profile of energy use, identify energy waste and develop measures to prevent it. Energy audit can be conducted on the use of electricity in a building, such as households. Electrical energy consumption in households tend to be wasteful because people cannot regulate electric energy consumption in households. Electrical energy consumption could be reduced if energy use had been planned earlier. Therefore, in this study focused on opportunities saving electrical energy by conducting energy audits. From the results of energy audits can be arranged steps and strategies that will be done in order to obtain saving electrical energy consumption in households. Beside it, this study also will be obtained a system which can be directly applied in the community. The method performed in this study is to create a new system which was performed on the system load replacement lamp, magic com, televisisons, computers and implement energy management strategies. Energy management strategy adopted is to change the paint color froam a dark room with bright colors, adding a new window and redigning the room based on standards set by IEEE 802.3az. from the resulting new system can occur energy savings of 65.4% compared to the old system.